2021
DOI: 10.1093/aje/kwab065
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Gestational Exposure to Toxicants and Autistic Behaviors Using Bayesian Quantile Regression

Abstract: Autism Spectrum Disorder, which is characterized by impaired social communication and stereotypic behaviors, affects 1-2% of children. While prenatal exposure to toxicants has been associated with autistic behaviors, most studies have focused on shifts in mean behavior scores. We used Bayesian quantile regression to assess the associations between log2-transformed toxicant concentrations and autistic behaviors across the distribution of behaviors. We used data from the Maternal-Infant Research on Environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 66 publications
0
37
0
Order By: Relevance
“…47 On the other hand, several studies found that urinary phthalate metabolite concentrations during pregnancy were associated with social impairment, which represents a key feature of ASD diagnosis. 22,36,48 We detected mixture associations in the opposite directions in the two cohorts. One possible reason is that these two cohorts had different study designs.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…47 On the other hand, several studies found that urinary phthalate metabolite concentrations during pregnancy were associated with social impairment, which represents a key feature of ASD diagnosis. 22,36,48 We detected mixture associations in the opposite directions in the two cohorts. One possible reason is that these two cohorts had different study designs.…”
Section: Discussionmentioning
confidence: 88%
“…47 On the other hand, several studies found that urinary phthalate metabolite concentrations during pregnancy were associated with social impairment, which represents a key feature of ASD diagnosis. 22,36,48…”
Section: Discussionmentioning
confidence: 99%
“…26 In Bayesian quantile regression models, lead, cadmium and most phthalate metabolites were associated with mild increases in SRS scores at the 90th percentile and above (worst SRS scores) while manganese and some pesticides were associated with mild decreases in SRS scores at this percentile. 46 Several investigations have examined the associations between prenatal exposure to a number of chemicals and child IQ.…”
Section: Child Neurodevelopmentmentioning
confidence: 99%
“…Nervous system : Using data from the Maternal-Infant Research on Environmental Chemicals study, a pan-Canadian cohort (2008–2011), no association was found between gestational urinary triclosan levels and the social responsiveness scale in children aged 3–4 ( n = 487) ( Alampi et al, 2021 ) [C].…”
Section: Triclosan [Seda-37 276; Seda-39 212; Seda-40 292; Seda-41 25...mentioning
confidence: 99%